Effect of 13 traditional Chinese medicine drug preparations against Neisseria gonorrhoeae - Liao, Wenfeng; Zhou, Ke; Zhang, Yan; Huang, Yuanqin; Zhang, Xia; Yin, Yueping; Zhou, Qian; Chen, Shaochun; Li, Weiyun; Xu, Wenqi (Frontiers in Pharmacology, 2025)
IntroductionGonorrhea poses severe health complications, with an estimated 82.4 million new adult infections reported globally in 2020. Currently, ceftriaxone monotherapy remains the first-line treatment in China. However, rising antimicrobial drug resistance necessitates has spurred the urgent need to explore novel therapeutic strategies. This study assessed the antibacterial activity of 13 traditional Chinese medicines (TCMs) against Neisseria gonorrhoeae (N. gonorrhoeae), aiming to identify alternative agents to combat antimicrobial drug resistance.MethodsThe minimum inhibitory concentrations (MICs) of 13 TCMs on 280 N. gonorrhoeae isolates were determined using the agar dilution method. The correlation between the MICs of TCMs and those of antibiotics was analyzed using the correlation coefficient (R value). The chemical profiles of TCMs were identified using Gas Chromatography-Mass Spectrometry (GC-MS) and Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS). The MICs of representative chemical metabolites on 53 N. gonorrhoeae isolates were determined using the agar dilution method.ResultsCoptidis Rhizoma (CR) exhibited the lowest MIC10 of ≤0.06 mg/mL and lowest MIC90 of ≤0.5 mg/mL. Six TCMs showed no correlation with the MIC values of ceftriaxone, spectinomycin or azithromycin.DiscussionThis study represents the first report about the antibacterial activity of these 13 TCMs against N. gonorrhoeae. The results indicate that CR, Phellodendri Chinensis Cortex (PCC), Forsythiae Fructus (FF), Taraxaci Herba (TH), and Scutellariae Radix (SR) exhibited good antibacterial activity against N. gonorrhoeae, highlighting their potential as promising therapeutic options for gonococcal infections. In contrast, the MICs of Bupleuri Radix (BR), Cimicifugae Rhizoma (CFR) showed correlations with those of ceftriaxone, azithromycin, and spectinomycin, suggesting that they may be unsuitable for monotherapy of gonococcal infections, given the potential risk of cross-resistance. Nevertheless, further in vitro experiments and clinical studies are required to validate these observations.